Impact of craniofacial skeletal characteristics on temporomandibular joint’s articular disc position in temporomandibular disorders - Almustafa Osama; Mazen Musa; Hai Juan Zhang; Cheng Dong Zheng; Mahmoud Nasih; Yu Han Ren; Shuang Wang (Scientific Reports)
Abstract This retrospective study aims to: (1) determine whether craniofacial skeletal characteristics differ based on the type of temporomandibular joint (TMJ) disc displacement (DD); and (2) identify cephalometric variables that correlate with and predict articular disc position. A total of 294 joints corresponding to 147 female patients, aged 18 to 41 years, were included. Based on the criteria of DC/TMD and subsequently magnetic resonance imaging (MRI) findings, the joints were categorized into three groups: 1) bilateral normal disc position (BN), 2) disc displacement with reduction (DDR), and 3) disc displacement without reduction (DDWR). The lateral cephalograms were assessed, and twelve landmarks were marked on each radiograph, from which fifteen variables were derived. Cone beam computed tomography (CBCT) images were evaluated for joint spaces, glenoid fossa characteristics, and condylar inclination. One-way ANOVA and post-hoc Tukey tests were used to compare variables across groups. Bivariate Pearson correlation analysis was conducted to assess relationships between glenoid fossa characteristics, disc position, condylar position, and skeletal morphology. Multiple linear regression (MLR) was applied to determine cephalometric predictors of disc position. Significant differences were observed in joint spaces, condylar inclination, and fossa morphology across the three groups. ANB, FMA, y-axis, gonial angle, and ramus height showed significant correlations with disc position. MLR demonstrated that FMA, ramus height, and articular angle were the strongest predictors of DD, particularly in DDWR, with an explanatory power of 55% (R2 = 0.55, p < 0.001). Craniofacial morphology plays a key role in the pathophysiology of DD. Patients with a steeper mandibular plane (higher FMA) and reduced ramus height were more prone to DDWR. These findings highlight the importance of cephalometric evaluation in assessing TMD and predicting disc position.